2019
DOI: 10.1016/j.chemosphere.2019.124391
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen micropollutant: Historical and current occurrences, toxicity, removal strategies and transformation pathways in different environments

Abstract: Acetaminophen (ACT) is commonly used as a counter painkiller and nowadays, it is increasingly present in the natural water environment. Although its concentrations are usually at the ppt to ppm levels, ACT can transform into various intermediates depending on the environmental conditions. Due to the complexity of the ACT degradation products and the intermediates, it poses a major challenge for monitoring, detection and to propose adequate treatment technologies. The main objectives of this review study were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(37 citation statements)
references
References 107 publications
(88 reference statements)
0
29
0
Order By: Relevance
“…The non-steroidal anti-inflammatory drugs such as diclofenac, acetaminophen, ibuprofen, naproxen, carbamazepine, trimethoprim, and lipid regulators including bezafibrate and clofibric acid-metabolite were classified as harmful contaminants, to aquatic organisms, ofloxacin, sulfamethoxazole, erythromycin, and oxytetracycline fall under toxic contaminants, while those with extremely low concentration had no adequate information to establish their impact on the environment and biota. Long-term exposure to acetaminophen, one of the most consumed PPCPs globally has been considered to cause cancer, endocrine disruption, and other several chronic diseases (Phong Vo et al 2019 ). Also, among the micropollutants that are common to the United States, European Union, and China, antiretroviral Efavirenz and octocrylene were found to have the highest aquatic HazPi value, an index for measuring the persistence, bioaccumulation, bioactivity, and toxicity of emerging micropollutants (Fang et al 2019 ).…”
Section: Risk and Ecotoxicological Assessments Bioremediation Treatme...mentioning
confidence: 99%
See 1 more Smart Citation
“…The non-steroidal anti-inflammatory drugs such as diclofenac, acetaminophen, ibuprofen, naproxen, carbamazepine, trimethoprim, and lipid regulators including bezafibrate and clofibric acid-metabolite were classified as harmful contaminants, to aquatic organisms, ofloxacin, sulfamethoxazole, erythromycin, and oxytetracycline fall under toxic contaminants, while those with extremely low concentration had no adequate information to establish their impact on the environment and biota. Long-term exposure to acetaminophen, one of the most consumed PPCPs globally has been considered to cause cancer, endocrine disruption, and other several chronic diseases (Phong Vo et al 2019 ). Also, among the micropollutants that are common to the United States, European Union, and China, antiretroviral Efavirenz and octocrylene were found to have the highest aquatic HazPi value, an index for measuring the persistence, bioaccumulation, bioactivity, and toxicity of emerging micropollutants (Fang et al 2019 ).…”
Section: Risk and Ecotoxicological Assessments Bioremediation Treatme...mentioning
confidence: 99%
“…There have been different technologies and techniques for the treatment of wastewater containing PPCPs, especially via wastewater treatment plants, which include sand filtration, sorption (adsorption and absorption), coagulation, ultrafiltration, advanced oxidation processes, ozone and ultraviolet light photolysis, bioremediation, and chlorine disinfection (see Table S6) Awfa et al ( 2019 ) He et al ( 2016 ). The removal efficiency of various PPCPs, however, is dependent on the appropriateness of the technology implemented in the wastewater treatment plants and other various factors which include system configuration, operation and treatment conditions, and influent loadings, making it difficult to compare removals of micropollutants in different treatment plants (Nam et al 2014 ; Phong Vo et al 2019 ). Nam et al also reported the influence of seasonality in the concentrations of micropollutants in the influent of treatment plants, with metoprolol, one of the highly used beta-blockers, exhibiting recalcitrant and persistency during the treatment process (removal efficiency of 6%) (Nam et al 2014 ).…”
Section: Risk and Ecotoxicological Assessments Bioremediation Treatme...mentioning
confidence: 99%
“…This suggests that the parent compound can transform and degrade partially due to external factors, including photolytic removal [38]. Moreover, microorganisms can play an important role in the rhizosphere which have established effective strategies involving specialized enzyme systems and metabolic pathways to access paracetamol as a carbon and energy source, producing some intermediate metabolites such as aromatic derivatives or organic acids [39,40].…”
Section: Mass Balancementioning
confidence: 99%
“…Thus, quests for successful mitigation processes to achieve the complete remediation of this emerging class of pollutants from the environment and water have resorted to AOPs of which EF is a subset. 7 14 EF has recently been applied in the removal of various pharmaceuticals and bacteria in effluent water in Colombia by Martínez and co-authors. 15 More similar work in the degradation of pharmaceuticals in wastewater was reported by Emeji and colleagues 16 in the removal of antiretroviral drugs, while Wang and co-authors used EF in separate work for the removal of ciprofloxacin and an antibiotic (cefoperazone), respectively.…”
Section: Introductionmentioning
confidence: 99%